MAKNA TEOLOGIS NOKEN DALAM BUDAYA ORANG MEE - Bobii, Silfester (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
In this paper I describe and discuss: the theological meaning of noken inthe culture of the Mee people. The method used is literature. Which isthen collected, grouped and managed and worked on based on books andscientific articles that are obtained related to the theological meaning ofnoken. From the study I worked on, it was found that noken has a veryimportant and deep theological meaning in the culture of the Mee tribeand in general in Papua. With this finding, it criticizes hidden acts ofhumanity’s murder as well as those seen during the selection of the nokensystem. In addition, it builds divine values from God contained in thenoken from an asset culture in Papua.